Tau Tau dalam Ritual Tradisi Maccera Manurung di Desa Pasang Kabupaten Enrekang - Suherman suherman; Muliyadi Muliyadi (Universitas Muhammadiyah Enrekang, 2020)
Maccera Manurung tradition ritual is a traditional culture that still exists today in the village of Pasang, as well as the ethnic identity of Massenrempulu. In the Maccera Manurung tradition, especially in the village of Pasang, there is the art of Tau Tau which makes the Maccera Manurung tradition in the village of Pasang different from the traditions of Maccera Manurung in other regions/regions that hold it. This research examines the art of Tau Tau in the Maccera Manurung tradition ritual in the village of Pasang as one of the traditional ritual arts, namely in terms of urgency and function. This research is a qualitative research using data techniques such as observation, interview, and documentation. The data validation technique used is triangulation, with an interactive model analysis technique. The results of this study indicate that: 1). Tau Tau art in the Maccera Manurung tradition ritual in the village of Pasang is very important and urgent because it is a complement to the ritual, namely as the personification of To Manurung; 2) The Tau Tau art in the Maccera Manurung tradition ritual in the village of Pasang has several functions, including: as a means or means of rituals, as a means of fulfilling the spiritual-religious needs of the village community, as a means of expression of spiritual-religious experiences of the residents of the village community, and as new in the activities or behavior patterns of the village people collectively.